Mobile learning for delivering health professional education - Tudor Car, Lorainne (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: The objective of this review is to evaluate the effectiveness of mLearning educational interventions for delivering pre‐registration and post‐registration healthcare professional education. We will primarily assess the impact of these interventions on students’ knowledge, skills, professional attitudes and satisfaction.